Assimilação do IWV-GPS no Brasil: Otimização das estimativas do atraso zenital troposférico em tempo real - Sapucci, Luiz Fernando; Monico, João Francisco Galera [UNESP]; Machado, Luiz Augusto Toledo; Herdies, Dirceu Luis; De Souza, Rodrigo Augusto Ferreira (My University, 2007)
IWV (Integrated Water Vapor) values from the Brazilian Network for Continuous Monitoring (RBMC) of GPS (Global Positioning System) signals are additional sources of humidity information available for being used in Numerical Weather Prediction (NWP) models operating in the Brazilian meteorological centers. In order to obtain IWV-GPS values In an efficient approach, an optimization of the GPS data processing for estimating the ZTD values (Zenithal Tropospheric Delay) is involved, which should search for the best result with lowest computational cost. In this optimization process it Is necessary to determine the deal size of the so called slidlng-window data involved In the real time data processing, which must be the as small as possible but providing results with the required quality. In this paper is investigated the ideal size of such sliding-window. An experiment was carried out in which GPS sliding-windows of different sizes were evaluated using simulations of a real time data processing. Comparing the obtained results with those from post-processed GPS data. It is observed that a sliding-window containing 7 hours of GPS data generated the best results from the operational point of view (rms of 1.61 and 1.82 kg m-2 for latency of 60 and 120 minutes, respectively). © 2007 Sociedade Brasileira de Geofisica.
The IWV-GPS assimilation in Brazil: Optimization of the estimates of the zenithal tropospheric delay in real time
Keywords: Data assimilation; IWV-GPS; NWP; ZTD